Factors predicting on health behaviors among older adults with hypertension in community - Pholputta, Ladda; Toemjai, Thawatchai; Phenphol, Nitchapanrawee; Sayuen, Chanidawadee; Udobsat, Sattawas; Wongpimoln, Boonyada (Intelektual Pustaka Media Utama, 2024)
In Thailand the prevalence of hypertension continues to rise and health behavior of older adults is generally suboptimal. The purpose of this study was to identify the characteristics that can identify health behavior in older persons with hypertension. A cross-sectional design study was carried out on 123 hypertensive older persons in Koh Kaew Sub-District, Sela Phum District, Roi Et Province, who were chosen using a simple random selection procedure. In-person interviews with structured questionnaires were used for gathering data. This study utilized surveys to collect demographic information, health beliefs, and health habits. Percentage, mean, standard deviation, and stepwise multiple regression were used to evaluate the data. The results showed that there were four factors together predict and explain the variance of health behaviors among older adults with hypertension accounting R2 and adjusted R2 value were 44.10% and 42.20% with statistical significance including female (β=0.242, p=0.001), perceived susceptibility (β=0.419, p<0.001), perceived barriers (β=0.239, p=0.001), and perceived benefits (β=0.181, p=0.013). To improve quality of life among older persons with hypertension, this research proposed involving healthcare providers, families, and health volunteers in promoting their health habits.